Production Of Juvenile Hormone Iii (Jh Iii) From Cyperus Aromaticus Via Cell Suspension Culture Technique And Its Effect On Mosquito Larva, Aedes Aegypti - Lim , Pey Shan (2010)
Callus of Cyperus aromaticus was induced from the root explants using modified Murashige and Skoog (1962) medium supplemented with 5.5 mg/L NAA and 4.5 mg/L 2,4-D. Seven stable cell lines were selected from these root-derived calluses. Cell suspension cultures were then established from these selected cell lines. Optimum cell biomass and high Juvenile Hormone III (JH III) content could be produced via single stage cell culture system using a modified culture medium. JH III of the tested samples was detected with high performance liquid chromatography (HPLC). The optimum culture duration for the production of high cell biomass and JH III content was 12 days. The optimized culture medium was formulated via step-wise modification of macronutrients portion of the basic MS medium and plant growth regulators. All the selected cell lines grew well in this optimum medium which consisted of MS supplemented with 271.1 mM NH4NO3 + 15.4 mM KNO3 + 4.3 mM CaCl2.2H2O + 1.49 mM MgSO4.4H2O + 1.35 mM KH2PO4 + 3% sucrose + 5.5 mg/L NAA + 4.5 mg/L 2,4-D (MSB) medium.